Importance of Human Faecal Biobanking: From Collection to Storage - Lewandowska Izabela; Grzech Katarzyna; Krzysztoń-Russjan Jolanta (Postępy Mikrobiologii)
The freezing and storage conditions of faecal samples in biobanks influence the preservation of the integrity and stability of genetic material and play a crucial role in scientific and clinical research quality. In recent years, there has been a particular increase in the number of studies related to the gut microbiome and the importance of its impact on the functioning human body. The review includes research on faecal microbiota transplantation (FMT), microbiome analysis, ‘-omics’ research, cancer and parasites. The primary topic addressed in this research is the impact of storage conditions and freezing methods for faecal samples on the stability and diversity of the gut microbiome. Standardizing procedures for storing and analyzing faecal samples is essential to carry out this task. This standardization is not a goal but a necessity for the quality control of the storage of faecal samples to reach comparative results and to develop new diagnostic methods. Collected data presented here highlight a crucial step in microbiota research concerning optimizing biobanking conditions for faecal samples.